US – Iran Proxy War in Middle East Under Trump Administration - Jose, Hino Samuel; Fathun, La ode Muhamad (Journal of Political Issues, 2021)
The heated bilateral relation between Iran and the United States has brought the middle east into another level of problem. The divided geopolitical and regional interest of both countries has led to several and many multidimensional issues, ranging from political, security, and even to economic ones. This article discussed the Iran – US tension on their proxy conflict in the Middle East. This article employs the Regional Security Complex Theory to construct the events related to both states’ proxy conflicts. The polarized region for sure has drawn another line that seems to be more complexed for both countries to achieve mutual understanding and continued peacebuilding. The US withdrawal from JCPOA, killing of Soleimani, and Saudi Arabia – Iran Yemen proxy war exacerbated the status quo. This article perceived that the intertwined issues show how the traditional thought of security should be redefined as both countries try to gain bargaining power. Especially with Iran that was hindered very much by sanctions and embargo placed by the US. This article discusses many important issues on Iran, US, and Saudi Arabia involvement and their correlated dynamics within the UN. This article analyzed Trump’s leadership style in the Middle East and its implication from the proxy war to the Middle East security architecture.